1992
DOI: 10.1021/ja00030a008
|View full text |Cite
|
Sign up to set email alerts
|

The hydrosodalite system Na6+x[SiAlO4]6(OH)x.cntdot.nH2O: formation, phase composition, and de- and rehydration studied by 1H, 23Na, and 29Si MAS-NMR spectroscopy in tandem with thermal analysis, x-ray diffraction, and IR spectroscopy

Abstract: The structure of the heme o prosthetic group of Escherichia coli quinol oxidase (cytochrome o oxidase) has been unambiguously determined by preparation and characterization of its iron-free derivative porphyrin o dimethyl ester, or dimethyl 2,7,12,18-tetramethyl-3-[(4£,8£)-l -hydroxy-5,9,13-trimethyltetradeca-4,8,12-trienyl] -8-vinylporphine-13,17-dipropionate. The identity of this natural porphyrin dimethyl ester was established by 'H NMR, MS, IR, and RR spectroscopies as well as by comparisons with model com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 3 publications
11
76
0
1
Order By: Relevance
“…Generally, hydrosodalites contain a large variety of encapsulated molecules such as NaOH and H 2 O (Engelhardt et al, 1992). A sharp peak corresponding to the water deformation mode at ∼1650 cm −1 appears in the spectra.…”
Section: Ft-ir Analysis Of Synthesised Nanozeolite Sodalitementioning
confidence: 97%
“…Generally, hydrosodalites contain a large variety of encapsulated molecules such as NaOH and H 2 O (Engelhardt et al, 1992). A sharp peak corresponding to the water deformation mode at ∼1650 cm −1 appears in the spectra.…”
Section: Ft-ir Analysis Of Synthesised Nanozeolite Sodalitementioning
confidence: 97%
“…This synthesized basic sodalite transforms into hydrosodalite during washing of the sample. [28] The main reflections of the hydrosodalite are labeled by stars in Figure 2.…”
Section: The Synthesis Behavior Of Fa and Naalo 2 In Dependence Of Thmentioning
confidence: 99%
“…From common synthesis investigations with pure chemicals, it is known that basic sodalite forms if the alkalinity is too high. [18][19][20] As strong FA [27,28] Na-A: zeolite LTA PDF 39-222. [27] A: amorphous aluminosilicate.…”
Section: The Synthesis Behavior Of Fa and Naalo 2 In Dependence Of Thmentioning
confidence: 99%
“…Previously, the literature has reported that the excess addition of NaOH resulted in the formation of the HS phase and the prevention of the formation of other zeolitic phases. 20) It is possible to add additional NaOH, because unreacted Na + and OH ¹ ions can be removed during the aqueous-washing process.…”
Section: Effects Of the Na 2 O Molar Contentmentioning
confidence: 99%